Why Governance Matters: A Study on Governance Practices of Stock Exchanges in India - Amit Majumder (Research Synergy Foundation, 2021)
Historically the responsibility of ushering the practices of good governance, transparent management and effective control process for the corporate houses rests under the jurisdiction of those stock exchanges where the shares of the companies are listed. However, the very question of the management and governance of these stock exchange houses are always under the scanner across the globe in view of the limitations of their historic pattern of member-owned ‘non-profit’ kind of mutual organizational structure. The lacunae of that typical organizational structure was that their activities are primarily targeted towards members interests as well as that set up was not immune fully from the malice like insider trading and conflict of interest for office bearers and traders. In view of this following the global pattern the Union Government of India had decided for corporatization of stock exchanges thereby creating a separation of ownership, management and trading membership of stock exchanges which is formally known as demutualization and corporatization of stock exchanges. A committee was set up by the SEBI under the chairmanship of Justice M.H. Kania which had submitted the report in 2002 recommending corporatizations and demutualization of stock exchanges which become mandatory for every stock exchange in India to implement within a stipulated period of time. Against this backdrop the present study is conducted to make an overview of the present state of governance affairs of major stock exchanges in India. It has been observed that the corporatization and governance practices of the major bourses in India had followed governance practices like separation of the post of chairman and CEO, inclusion of public interest directors as outside directors in the board, adherence to code of conducts for directors, organizing frequent meetings of directors etc.